Unilateral macular edema with central retinal vein occlusion in systemic lupus erythematosus: a case report - Noma H (Dove Medical Press, 2013)
Hidetaka Noma,1 Hiroshi Shimizu,1 Tatsuya Mimura21Department of Ophthalmology, Yachiyo Medical Center, Tokyo Women's Medical University, 2Department of Ophthalmology, Medical Center East, Tokyo Women's Medical University, Tokyo, JapanAbstract: Central retinal vein occlusion (CRVO) is frequent in patients with systemic lupus erythematosus (SLE), but the treatment of the macular edema with this disease is extremely difficult. We report a case of cystoid macular edema (CME) secondary to unilateral CRVO in a patient with SLE that responded to intravitreous injection of an anti-vascular endothelial growth factor (VEGF) agent. A 33-year-old Japanese woman was referred to our department with unilateral impairment of vision. Microperimetry (MP-1) showed a cessation of foveal sensitivity. Fluorescein angiography showed CME without ischaemia of the macular region or peripheral retina (nonischemic CRVO). A diagnosis of CME and unilateral nonischemic CRVO combined with SLE was made and intravitreous anti-VEGF therapy was given. A sample of aqueous humor was harvested at the start of intravitreous injection after obtaining informed consent. Then the levels of VEGF and monocyte chemotactic protein (MCP)-1 were measured in the aqueous humor by enzyme-linked immunosorbent assay, revealing that VEGF was 234 pg/mL and MCP-1 was 501 pg/mL. Two weeks later, left eye vision improved to 20/20. Optical coherence tomography (OCT) showed considerable amelioration of retinal swelling and CME. MP-1 showed a marked increase of foveal sensitivity. However, she had recurrence of edema 3 months later. After harvesting aqueous humor again, intravitreous injection of an anti-VEGF agent was repeated for CME. The aqueous VEGF and MCP-1 levels were 156 pg/mL and 360 pg/mL, respectively. These findings suggest that inflammation was improved by intravitreous injection of bevacizumab. Intravitreous injection of anti-VEGF agents may be effective for CME due to nonischemic CRVO in SLE patients if their inflammatory factor levels are low..Keywords: systemic lupus erythematosus, central retinal vein occlusion, cystoid macular edema, anti-vascular endothelial growth factor agent, vascular endothelial growth factor, monocyte chemotactic protein-1